Analysis of Occupational Safety and Health (OSH) Management using The HIRARC Method in The Construction of Rubaru 1 Elementary School - Midi Agus Permana; Budi Witjaksana; Jaka Purnama (International Journal Labs, 2025)
Construction projects in Indonesia continue to face high rates of workplace accidents due to inadequate implementation of Occupational Safety and Health (OSH) systems. This study aims to analyze how the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method can be effectively applied in the Rubaru 1 Elementary School construction project to minimize risks and improve workplace safety. Using a qualitative descriptive approach, data were collected through field observations, interviews, and documentation studies over six months. The research identified multiple hazards categorized by severity: six major risks, three high risks, and six medium risks. These included hazards from working at heights, exposure to chemicals, and improper use of personal protective equipment (PPE). Risk controls were implemented through administrative strategies (training, supervision), engineering controls (equipment modifications, warning signs), and mandatory PPE usage. The results showed that the HIRARC method is effective in systematically identifying and mitigating construction-related hazards. However, its success is influenced by the discipline of workers and management’s commitment to supervision. The findings emphasize the need for continuous evaluation and structured training programs to enhance OSH compliance and cultivate a safety-oriented culture in construction environments.